The Influence and Role of Mother Tongue Transfer and Input Methods on Second Language Acquisition - Guo, Mengyu (International Journal of Social Sciences and Public Administration, 2024)
Second language acquisition mainly refers to the learning of any other language after acquiring the mother tongue, also known as second language acquisition. Only by possessing good theoretical knowledge of second language acquisition can we better leverage strengths and avoid weaknesses, and improve efficiency. In the process of second language acquisition, the influence of the mother tongue on learners is a common phenomenon that has gradually attracted attention and research. Mother tongue transfer means that learners apply the rules and methods of their mother tongue to second language acquisition. Mother tongue transfer mainly includes two types: positive transfer and negative transfer. This article mainly analyzes the positive and negative impacts of mother tongue transfer, and adopts correct strategies and methods to address them, demonstrating the importance of treating mother tongue transfer correctly in second language acquisition. In addition, input methods also affect the level of second language acquisition.